Synthesis and photochromic properties of a bis(diarylethene)-naphthopyran hybrid. (April 2015) - Erko, Firealem G.; Cseh, Liliana; Berthet, Jérôme; Mehl, Georg H.; Delbaere, Stéphanie
Abstract: The synthesis and photochromic properties of a triphotochromic molecule consisting of one naphthopyran flanked by two diarylethene units investigated by UV–Visible and Nuclear Magnetic Resonance spectroscopies are reported. Six different states resulting from the open/closed naphthopyran associated with one or two open/cyclized diarylethenes have been characterized. The photochemical and thermal interconversion between the six states of the triphotochromic target was followed allowing to determine the existing pathways upon irradiation with 313 and 365 nm light excitation, and during thermal evolution. Switching of the naphthopyran group is possible, independently of the state of the diarylethene groups. However, the diarylethene groups cannot be closed if the naphthopyran group is open. Graphical abstract: Highlights: New Triphotochromic bis-diarylethene-naphthopyran was synthesized. Photochromic response was investigated by UV–Visible and NMR spectroscopies. Six-state system was evidenced. Switching of the naphthopyran group is always possible. Switching of diarylethene requires closed configuration of naphthopyran.